Komponen Kepemimpinan Transformasional Dalam Meningkatkan Daya Tarik Pelanggan Pendidikan Islam - Zulfa, Hariratuz; Maunah, Binti; Fatoni, Achmad (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2024)
This research discusses the leadership components possessed by a transformational leader in enhancing the appeal of Islamic education customers. The study employs a library research approach by conducting a literature review relevant to the topic. The findings and discussion reveal that Transformational Leadership involves creating and initiating new thoughts and visions within an organization. Although there are many views on the meaning of Transformational Leadership, it is generally understood as an agent of change. The components of Transformational Leadership include charisma, the ability to encourage member creativity, individual consideration, and inspirational motivation. Effective marketing strategies can help Islamic educational institutions increase student enrollment and improve the institution's reputation. Therefore, Islamic educational institutions must continuously develop appropriate and effective marketing strategies by considering market developments and the needs of prospective students. It is hoped that this research will provide new breakthroughs for leaders in attracting customers to Islamic educational institutions.